Sliding member and piston ring

By forming a hard carbon coating with low hydrogen content and high thickness on the substrate, and adjusting the ratio of Martens hardness to indentation hardness, the problem of insufficient peel resistance and wear resistance in the prior art in the hard carbon coating with high thickness is solved, and a sliding member and piston ring with high durability are realized.

CN119615055APending Publication Date: 2025-03-14RIKEN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411641158.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-10-20
Filing Date
2018-10-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When the prior art improves the thickness of the hard carbon coating, it is difficult to take into account both high peel resistance and high wear resistance, especially when the thickness reaches 3 μm or more, there is room for improvement.

Method used

The hard carbon coating with a hydrogen content of 3 atomic % or less and a thickness of 3 μm or more was formed on the substrate by ion plating method, and the ratio of Martens hardness to indentation hardness (HM/HIT) was set to 0.40 or more to improve the density and wear resistance of the coating.

Benefits of technology

Even if the thickness reaches 3 μm or more, the sliding member and the piston ring have high peel resistance and high wear resistance, thereby significantly improving the durability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615055A_ABST
    Figure CN119615055A_ABST
Patent Text Reader

Abstract

The invention relates to a sliding member and a piston ring. Provided is a sliding member having a hard carbon coating film which has both high peeling resistance and high wear resistance even when the thickness is 3 [mu] m or more. This sliding member (100) is characterized by having a base material (10) and a hard carbon film (12) which is formed on the base material (10) and which has a hydrogen content of 3 atomic% or less and a thickness of 3 [mu] m or more, the Martens hardness of the hard carbon film (12) being HM and the indentation hardness being HIT, HM / HIT being 0.40 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese invention patent application with application number 201880058600.X (international application number PCT / JP2018 / 037593), Chinese national phase entry date March 10, 2020 (international application date October 9, 2018), and invention name “Sliding Component and Piston Ring”. Technical Field

[0002] The present invention relates to a sliding member having a hard carbon coating having both high peeling resistance and high wear resistance, and a piston ring including the sliding member. Background Art

[0003] In sliding parts such as piston rings, hardness and wear resistance are generally improved by coating a base material with a hard carbon coating such as a diamond-like carbon (DLC) coating.

[0004] Patent Document 1, one of the purposes of which is to provide a sliding component having a DLC coating with high hardness and excellent wear resistance, describes a sliding component having a substrate, an intermediate layer formed on the substrate, and a DLC coating formed on the intermediate layer with a thickness of 0.5 to 5 μm and a hydrogen content of 5 atomic % or less, preferably 2 atomic % or less. In Patent Document 1, the indentation hardness of the coating is preferably set to 20 to 70 GPa, and in order to suppress the defect and peeling of the coating, the Young's modulus of the coating is preferably set to 60 GPa or more.

[0005] Patent Document 2, one of the purposes of which is to provide a sliding member having a DLC coating with high wear resistance, describes a sliding member having a substrate, an intermediate layer formed on the substrate, and a DLC coating with a thickness of 0.15 to 6.0 μm formed on the intermediate layer. Patent Document 2 describes that when the Young's modulus of the coating exceeds 180 GPa, the coating is prone to rupture and peeling, and when the Young's modulus of the coating is less than 50 GPa, the load resistance during sliding is reduced, and describes that the surface hardness of the coating is preferably set to 20 to 140 GPa.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2006-250348

[0009] Patent Document 2: Japanese Patent Application Publication No. 2008-81522 Summary of the invention

[0010] Problems to be solved by the invention

[0011] In Patent Documents 1 and 2, in order to obtain a DLC film with high hardness and excellent wear resistance, the Young's modulus taking into account the strain when stress is applied and the indentation hardness taking into account the plastic deformation are adjusted to a specified range. However, in recent years, from the viewpoint of durability, the film tends to be thicker. If only focusing on the Young's modulus and the indentation hardness, respectively, when the film is set to 3 μm or more, there is room for improvement in terms of both high peeling resistance and high wear resistance.

[0012] In view of the above problems, an object of the present invention is to provide a sliding member having a hard carbon coating having both high peeling resistance and high wear resistance even when the thickness is 3 μm or more. Another object of the present invention is to provide a piston ring composed of the sliding member.

[0013] Methods used to solve problems

[0014] In order to solve the above-mentioned problem, the inventors conducted the following experiment: using an ion plating method that is effective in suppressing the hydrogen content of the coating to less than 3 atomic %, a hard carbon coating with a thickness of more than 3 μm was formed on a substrate. It was found that the denser the coating, the higher the peeling resistance and wear resistance. Based on the experimental results, the following idea was obtained: in order to improve the wear resistance of the coating, it may be important to focus on the Martens hardness of the elastic deformation that is correlated with the density. Furthermore, further research was conducted and it was found that by setting the ratio (HM / HIT) of the Martens hardness (HM) to the indentation hardness (HIT) to more than 0.40, a coating with excellent peeling resistance and wear resistance can be obtained.

[0015] The present invention has been accomplished based on the above findings, and its gist is as follows.

[0016] (1) A sliding member comprising a substrate and a hard carbon coating having a hydrogen content of 3 atomic % or less and a thickness of 3 μm or more formed on the substrate, wherein:

[0017] The Martens hardness of the hard carbon film is denoted as HM, and the indentation hardness is denoted as HIT, and HM / HIT is 0.40 or more.

[0018] (2) The sliding member according to the above (1), wherein the HIT is 15 GPa or more and 50 GPa or less.

[0019] (3) The sliding member according to (1) or (2) above, wherein the hard carbon film has a thickness of 5 μm or more.

[0020] (4) The sliding member according to any one of (1) to (3) above, wherein the surface roughness Ra of the hard carbon film is 0.12 μm or less.

[0021] (5) A sliding component as described in any one of (1) to (4) above, wherein an intermediate layer composed of one or more materials selected from Cr, Ti, Co, V, Mo and W, and their carbides, nitrides and carbonitrides is provided between the substrate and the hard carbon coating.

[0022] (6) A piston ring comprising the sliding member according to any one of (1) to (5) above.

[0023] Effects of the Invention

[0024] According to the present invention, a sliding member having a hard carbon coating having both high peeling resistance and high wear resistance even when the thickness is 3 μm or more can be obtained. In addition, according to the present invention, a piston ring composed of the sliding member can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 1 is a schematic cross-sectional view of a sliding member 100 according to an embodiment of the present invention.

[0026] Figure 2 This is a cross-sectional perspective view of a piston ring 200 according to an embodiment of the present invention.

[0027] Figure 3 This is a schematic diagram of a testing machine used in a sliding fatigue test. DETAILED DESCRIPTION

[0028] Below, reference Figure 1 , 2 One embodiment of the sliding member and the piston ring of the present invention will be described.

[0029] (Sliding member)

[0030] refer to Figure 1 The sliding member 100 of the present embodiment includes a substrate 10 and a hard carbon film 12 formed on the substrate 10 .

[0031] [Base material]

[0032] The substrate 10 in this embodiment is not particularly limited as long as it has the strength required as a sliding member, and examples thereof include conductive materials such as iron, cast iron, superhard alloy, stainless steel, and aluminum alloy. The substrate 10 may be further subjected to a hard coating or plating treatment of metal nitrides such as chromium nitride and titanium nitride, metal carbonitride, and metal carbide, or a hardening treatment such as quenching and tempering in the case of an iron-based material, or a nitriding treatment. For example, the piston ring is preferably made of martensitic stainless steel, spring steel, carbon steel, and the like that have been used in the past.

[0033] [Hard Carbon Coating]

[0034] The hard carbon film 12 in the present embodiment is a diamond-like carbon (DLC: Diamond Like Carbon) film 12 .

[0035] The hydrogen content of the DLC film 12 is 3 atomic % or less. This is because when the hydrogen content exceeds 3 atomic %, sufficient hardness and wear resistance cannot be obtained. The hydrogen content can be measured using HFS (Hydrogen Forward Scattering) method or the like.

[0036] The thickness of the DLC film is 3 μm or more. This is because, when the thickness is less than 3 μm, sufficient durability cannot be obtained. The thickness of the DLC film is more preferably 5 μm or more. It should be noted that the thicker the thickness of the DLC film, the longer the film forming time is required. Therefore, from the perspective of productivity, it is preferably set to 30 μm or less. The thickness of the film can be obtained by observing the cross section of the film using a SEM (Scanning Electron Microscope).

[0037] When the Martens hardness of the DLC coating 12 is HM and the indentation hardness is HIT, the ratio of these, HM / HIT, is 0.40 or more. In the present embodiment, for a DLC coating having a hydrogen content of 3 atomic % or less and a thickness of 3 μm or more, it is important that HM / HIT is 0.40 or more. The technical meaning thereof is described below.

[0038] Based on the experimental results described above that the higher the density of the DLC film with a hydrogen content of less than 3 atomic % and a thickness of more than 3 μm, the higher the peeling resistance and wear resistance are, the inventors have obtained the following conception: In order to take into account both high peeling resistance and high wear resistance, it is important to focus on the Martens hardness of elastic deformation that is considered to have a strong correlation with density. That is, the indentation hardness (HIT) is an index of hardness (plastic hardness) based on plastic deformation like Vickers hardness, and it is believed that it has a correlation with the tensile strength (film strength) of the film itself. On the other hand, the Martens hardness (HM) is based on the hardness (elastic-plastic hardness) of elastic-plastic deformation that also considers elastic deformation, and is greatly affected by the rigidity of the film and the compressive residual stress inside the film. Here, there is a tendency that the higher the density, the higher the rigidity and compressive residual stress. In addition, with respect to the wear resistance of the film, it is basically important to improve the plastic hardness, but when the plastic hardness is too high, it is easy to show brittle characteristics, and it is easy to increase the wear amount based on extremely small cracks. In addition, the peeling of the coating occurs based on the cracks generated by the elastic-plastic deformation of the coating itself. The optimal rigidity range of the coating changes depending on whether the sliding environment is a constant stress action system or a constant strain action system. In a general sliding environment, there are more constant stress action systems. Therefore, the higher the rigidity of the coating, the more it can suppress the generation of cracks, and the peeling resistance is mostly excellent. As mentioned above, it was found that in order to play a good characteristic as a sliding component, the balance of the Martens hardness (HM), which is an index of compactness that is considered to have a strong correlation with the rigidity and residual stress of the coating, and the indentation hardness (HIT), which is an index of plastic hardness that has a correlation with the strength of the coating, is important. It should be noted that the indentation hardness (HIT) is also somewhat affected by the compactness that is considered to have a strong correlation with the rigidity and residual stress of the coating, but the influence will not be as great as the influence on the Martens hardness (HM). Therefore, the results of experimentally studying these indicators show that by setting HM / HIT to more than 0.40, a coating that takes into account both high peeling resistance and high wear resistance can be obtained. It is more preferable to set HM / HIT to 0.40 or more and 0.55 or less.

[0039] It should be noted that HIT is preferably set to be greater than 15 GPa and less than 50 GPa. When it is greater than 15 GPa, sufficient strength can be obtained. In addition, when it is less than 50 GPa, there is no need to worry about the film showing brittle characteristics, and a film with excellent wear resistance can be obtained. In addition, HM is preferably set to be greater than 6 GPa and less than 20 GPa. When it is greater than 6 GPa, the compactness can be improved, and therefore, a film with excellent peeling resistance can be obtained. When it is less than 20 GPa, there is no need to worry about the film peeling even if the film thickness is thickened.

[0040] "Indentation hardness (HIT)" and "Martens hardness (HM)" in this specification are based on the nano-indentation hardness test method specified in the international standard ISO14577. Specifically, a diamond indenter with a tip shape of a regular triangular pyramid (Berkovich type) is pressed into the surface of the coating, and the load applied to the indenter and the displacement of the indenter are continuously obtained to obtain a "load-displacement curve". Then, based on the calculation method recorded in ISO14577, indentation hardness (HIT) and Martens hardness (HM) are obtained. It should be noted that, in order to avoid the influence of the base material of the coating substrate, the indentation load is set in a manner such that the maximum indentation depth of the diamond indenter is less than 1 / 10 of the film thickness. In addition, as a pre-treatment of the test, mirror polishing is implemented to the test site, thereby suppressing the fluctuation of the test value.

[0041] The DLC film 12 having such characteristics can be formed on the substrate 10 by, for example, an ion plating method based on vacuum arc discharge using a carbon target. Hereinafter, a method for forming the DLC film 12 will be described.

[0042] Generally speaking, in ion plating, 1×10 -1 In a vacuum atmosphere below Pa, a carbon cathode is evaporated and ionized by vacuum arc discharge, thereby depositing ionized carbon on the surface of a substrate 10 to which a negative bias voltage is applied. Thus, a DLC coating 12 is formed on the substrate 10. According to the ion plating method, unlike the chemical vapor deposition (CVD: Chemical Vapor Deposition) method using hydrogen-containing carbides such as methane as raw materials, the raw materials do not contain hydrogen, so the hydrogen content of the coating can be suppressed to less than 3 atomic %. It should be noted that the ion plating method also includes the so-called FCVA (Filtered Cathodic Vacuum Arc) method in which a magnetic filter is used to capture and remove carbon that is not ionized during evaporation. Here, the value of HM / HIT does not depend on the presence or absence of a magnetic filter.

[0043] In the present embodiment, it is important to set HM / HIT to be greater than 0.40, which can be achieved by adjusting the bias voltage and the arc discharge current within the following range. The bias voltage is set to be greater than -50V and less than 0V. When the bias voltage is lower than -50V, the increase in HM shows a decreasing trend relative to the increase in HIT, and HM / HIT is less than 0.40. In addition, the arc discharge current is set to be greater than 50A and less than 200A. When it is lower than 50A, a dense DLC coating cannot be formed, so the increase in HM decreases relative to the increase in HIT, and HM / HIT is less than 0.40. By setting the arc discharge current to less than 200A and implementing appropriate discharge termination to prevent the increase in substrate temperature, there is no need to worry about a decrease in the hardness of the DLC coating, and HIT can be made greater than 15GPa and HM can be made greater than 6GPa. Here, within the range of -50 V to 0 V and 50 A to 200 A, when the absolute value of the bias voltage increases, HM / HIT decreases, and when the arc discharge current increases, HM / HIT increases. It should be noted that the temperature of the substrate is preferably set to 100° C. to 230° C.

[0044] The thickness of the DLC film 12 can be controlled by the arc discharge time.

[0045] As mentioned above, the sliding member of the present invention has been described by taking the present embodiment as an example, but the present invention is not limited to the above-mentioned embodiment and can be appropriately modified within the scope of the claims.

[0046] For example, in order to improve the adhesion of the hard carbon coating to the substrate, an intermediate layer composed of one or more materials selected from Cr, Ti, Co, V, Mo and W, and their carbides, nitrides and carbonitrides can be provided between the substrate and the hard carbon coating. The thickness of the intermediate layer is preferably greater than 0.01 μm and less than 0.6 μm, and more preferably greater than 0.02 μm and less than 0.5 μm. This is because, when it is greater than 0.01 μm, the adhesion of the hard carbon coating can be improved, and when it is less than 0.6 μm, the intermediate layer is not easy to plastically flow during sliding, and the hard carbon coating is not easy to peel off. The intermediate layer can be formed on the substrate by, for example, appropriately using any or known PVD (physical vapor deposition) method.

[0047] In addition, from the viewpoint of further suppressing the wear amount of the object member during sliding, it is preferred to set the surface roughness Ra of the DLC coating 12 to 0.12 μm or less. Such surface roughness can be achieved by performing any or known grinding on the surface of the DLC coating. It should be noted that the "surface roughness Ra" in this specification refers to the arithmetic mean roughness Ra specified in JIS B 0601 (2001).

[0048] (Piston ring)

[0049] refer to Figure 2 The piston ring 200 according to one embodiment of the present invention is composed of the above-mentioned sliding member 100, and its outer peripheral surface 20 is Figure 1 The piston ring 200 has a DLC-coated surface 12A. Since the outer peripheral surface 20, which is the sliding surface, is a DLC-coated surface 12A that has both high peeling resistance and high wear resistance, the piston ring 200 has excellent peeling resistance and wear resistance even in a high-load sliding environment. It should be noted that the inner peripheral surface 22 and the upper and lower surfaces 24A and 24B of the piston ring do not need to be set to Figure 1 The structure shown.

[0050] The sliding member 100 according to an embodiment of the present invention can be applied not only to piston rings but also to valve lifters and gaskets as valve components of internal combustion engines such as automobiles, piston pins as components of internal combustion engines, and impellers for compressors and hydraulic pumps.

[0051] [Example]

[0052] For each of the inventive examples and comparative examples, Figure 2 The piston rings were produced under the following conditions so that the outer peripheral surface of the piston ring shown in Table 1 became the surface of the DLC film.

[0053] In each of the inventive examples and comparative examples, a 0.4 μm thick intermediate layer made of chromium was formed on a silicon-chromium steel substrate having a nominal diameter of 90 mm, a thickness of 2.9 mm, and a width of 1.2 mm using a known PVD method. - 1 In a vacuum atmosphere of less than 1.5 Pa, an ion plating method based on vacuum arc discharge using a carbon target was used, and the bias voltage, arc discharge current, and arc discharge time were appropriately adjusted within the ranges described above, thereby forming a DLC film shown in Table 1 on the intermediate layer. However, only for Comparative Example 4, DLC film formation based on the carbon sputtering method was performed while introducing hydrocarbon gas.

[0054] (Explanation of evaluation methods and evaluation results)

[0055] In each invention example and comparative example, the thickness, surface roughness, HM and HIT of the DLC coating are obtained by the method described above. The nanoindentation hardness tester uses ENT-1100a manufactured by ElioniX. In addition, HM / HIT is calculated using the test values ​​of HM and HIT. It should be noted that in the test of HM and HIT, the indentation load is set to 50mN in invention examples 1 to 6, 8 and comparative examples 1 to 4, and the indentation load is set to 6mN in invention example 7 and comparative example 5, so that the maximum indentation depth of the diamond indenter is less than 1 / 10 of the film thickness.

[0056] In addition, in each of the invention examples and comparative examples, the hydrogen content of the DLC coating is evaluated by the following method. In the evaluation of the hydrogen content of the DLC coating, for a DLC coating formed in a flat area or an area with a sufficiently large radius of curvature that is considered to be a plane in measurement, RBS (Rutherford Backscattering Spectrometry) / HFS (Hydrogen Forward Spectrometry) can be used for evaluation. In contrast, for a DLC coating formed in an uneven area such as the outer peripheral surface of a piston ring, RBS / HF can be combined with SIMS (Secondary Ion Mass Spectrometry) for evaluation. RBS / HFS is a well-known method for analyzing the composition of a coating, but cannot be applied to the analysis of an uneven surface, and therefore, RBS / HFS is combined with SIMS as follows.

[0057] First, a DLC coating to be measured as a reference value is formed on a flat test piece (SKH51 disc with quenching treatment, φ25×thickness 5mm, hardness HRC60-63) after mirror polishing by the method described above, as a reference sample with a flat surface. Then, their hydrogen content is evaluated by RBS / HFS. On the other hand, the DLC coating of each invention example and comparative example is analyzed by SIMS to measure the secondary ion intensity of hydrogen. It should be noted that SIMS analysis can also be performed on a coating formed on an uneven surface such as the outer peripheral surface of a piston ring. Then, for the same coating as the reference sample, an empirical formula (calibration curve) is obtained to represent the relationship between the hydrogen content (unit: atomic %) obtained by RBS / HFS and the secondary ion intensity of hydrogen obtained by SIMS. By doing this, the hydrogen content can be calculated based on the secondary ion intensity of hydrogen of SIMS measured on the outer peripheral surface of the actual piston ring. It should be noted that the value of the secondary ion intensity based on SIMS adopts the average value of the secondary ion intensity of hydrogen observed within a range of 50 nm square at a depth of at least 20 nm from the coating surface. The hydrogen content of the DLC coating calculated in this way is shown in Table 1. It should be noted that the "3 atomic % or less" shown in Table 1 means that although the actual analysis values ​​are all less than 1 atomic %, they are expressed as "3 atomic % or less" in consideration of the measurement error.

[0058] In addition, in each of the inventive examples and comparative examples, wear resistance and peeling resistance were evaluated by the following method: That is, a sliding fatigue test was performed as an evaluation of peeling and wear that can quickly reproduce a real machine test. Figure 3 The outline of the testing machine is shown in FIG. In the sliding fatigue test, by repeatedly applying load to the rotating drum 30 and the sliding test piece 32, the peeling resistance and wear resistance of the coating can be confirmed in a relatively short time. Here, the test piece 32 is a test piece obtained by cutting each piston ring in a manner such that a part of the outer peripheral surface of the piston ring in each invention example and comparative example becomes the sliding surface in the sliding fatigue test. The wear resistance is evaluated by measuring the wear depth of the sliding surface of the test piece 32 before and after the test. In addition, the presence or absence of peeling of the sliding surface of the test piece 32 is observed using an optical microscope to evaluate the peeling resistance. The evaluation results are shown in Table 1. It should be noted that the test conditions are as follows.

[0059] Load: 20~196N, sine curve 50Hz

[0060] Target component (drum): SUJ2 material with a diameter of 80 mm

[0061] Sliding speed: forward and reverse mode operation (±7m / s), maintain 20s at a speed of ±7m / s

[0062] Acceleration: 0.23m / s 2

[0063] Lubricant: No additive motor oil, 0.1cc / min

[0064] Temperature: Drum surface temperature 80℃

[0065] Test time: 1 hour

[0066]

[0067] In Comparative Example 4, in which the hydrogen content of the DLC coating does not meet the range of the present invention, and Comparative Example 5, in which the coating thickness does not meet the range of the present invention, the wear depth is deep and the wear resistance is poor. In particular, the DLC coating and the intermediate layer of these examples are worn away, and a part of the substrate is worn. In addition, in Comparative Examples 1 to 3, even if the hydrogen content and thickness of the DLC coating meet the range of the present invention, since HM / HIT is less than 0.40, the wear depth is deep and the wear resistance is poor compared with Invention Examples 1 to 8. In addition, in Comparative Examples 1 to 3 and Comparative Example 5, micro peeling is confirmed in the sliding part. In addition, when comparing Invention Example 2 and Comparative Example 1, in which the hydrogen content and thickness of the DLC coating are roughly the same, Invention Example 2 with HM / HIT of 0.40 or more can more significantly suppress the wear depth and no peeling occurs compared with Comparative Example 1 with HM / HIT of less than 0.40. Similarly, when comparing Invention Example 3 and Comparative Example 3, which have approximately the same hydrogen content and thickness of the DLC coating, Invention Example 3, in which HM / HIT is greater than 0.40, can significantly suppress the wear depth and does not peel off. In contrast, in Comparative Example 3, in which HM / HIT is less than 0.40, the DLC coating is worn away, a portion of the substrate is exposed, and there is slight peeling on the remaining portion of the coating.

[0068] Industrial Applicability

[0069] According to the present invention, a sliding member having a hard carbon coating having both high peeling resistance and high wear resistance even when the thickness is 3 μm or more can be obtained. In addition, according to the present invention, a piston ring having the sliding member can be obtained.

[0070] Explanation of symbols

[0071] 100 Sliding components

[0072] 10. Substrate

[0073] 12 Hard carbon coating (DLC coating)

[0074] 12A Sliding surface

[0075] 200 Piston ring

[0076] 20 Outer Surface

[0077] 22 Inner Surface

[0078] 24A, 24B upper and lower surfaces

[0079] 30 Drums

[0080] 32 test pieces

Claims

1. A sliding member comprising a substrate and a hard carbon coating having a hydrogen content of 3 atomic % or less and a thickness of 3 μm or more formed on the substrate, characterized in that: The Martens hardness of the hard carbon film is HM, the indentation hardness is HIT, HM / HIT is 0.40 or more, HIT is 15 GPa or more, and HM is 6 GPa or more. The hard carbon film is formed by ion plating under the conditions that the bias voltage is not less than -50 V and not more than 0 V, the arc discharge current is not less than 50 A and not more than 200 A, and the temperature increase of the substrate is prevented by appropriate discharge suspension.

2. The sliding member according to claim 1, wherein: The HIT is 50 GPa or less.

3. The sliding member according to claim 1 or 2, wherein: The hard carbon film has a thickness of 5 μm or more.

4. The sliding member according to claim 1 or 2, wherein: The surface roughness Ra of the hard carbon film is 0.12 μm or less.

5. The sliding member according to claim 1 or 2, wherein: An intermediate layer composed of one or more materials selected from the group consisting of Cr, Ti, Co, V, Mo, and W, and carbides, nitrides, and carbonitrides thereof is provided between the substrate and the hard carbon film.

6. The sliding member according to claim 1 or 2, wherein: The hard carbon film has a thickness of 12 μm or more. 7 . A piston ring comprising the sliding member according to claim 1 .

Citation Information

Patent Citations

  • Sliding member

    JP2006250348A

  • Slide member

    JP2008081522A